Effects of Preweaning Polysensorial Enrichment Upon Development of the Parietal Cortical Plate of Undernourished Rats: A Stereological Study [Efectos del Enriquecimiento Ambiental Predestete Sobre el Desarrollo de la Placa Cortical Parietal de Ratas Desnutridas: Estudio Estereológico] - Hernandez-Kunstmann, A (Universidad de la Frontera, 2014)
This investigation was undertaken in order to quantify the effects of early polysensorial enrichment on the development of cortical pyramids, located in the parietal cortex of rats simultaneously submitted to protein-energy undernutrition. A short period of stimulation during suckling significantly decreases the cellular density in the cortical plate (phylogenetic-ontogenetic evolutionary index). Results suggest that the cerebral cortex develops according to a sophisticated neuronal network, which exhibits a notable degree of structural specificity, regulated by genetic and environmental clues. The most obvious prediction is that environmental influences are probably transduced as a structural expression in the developing parietal cortical plate. © 2014, Universidad de la Frontera. All rights reserved.
Keywords: Environmental enrichment; Cortical gradients; Undernutrition; Parietal cortex; Stereology